2017
DOI: 10.1002/hbm.23732
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PASL, PCASL, and background‐suppressed 3D PCASL in mild cognitive impairment

Abstract: We compared three implementations of single-shot arterial spin labeled (ASL) perfusion magnetic resonance imaging (MRI): two-dimensional (2D) pulsed ASL (PASL), 2D pseudo-continuous ASL (PCASL), and background suppressed (BS) 3D PCASL obtained in a cohort of patients with mild cognitive impairment (MCI) and elderly controls. Study subjects also underwent 18F-flurodeoxyglucose positron emission tomography (18F-FDG PET). While BS 3D PCASL showed the lowest (p<0.001) gray matter-white matter cerebral blood flow (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 74 publications
(115 reference statements)
3
52
1
Order By: Relevance
“…This approach will be useful especially for studies that have large sample size (Habes et al, 2016), where reacquiring missing imaging modalities from the same subject is not practical. CBF estimation was better at the posterior regions, where many previous studies (Alsop et al, 2008;Dolui et al, 2017;Huang et al, 2018) and our results showed altered CBF in MCI or Alzheimer's pathology, suggesting the potential use of proposed method in those populations.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…This approach will be useful especially for studies that have large sample size (Habes et al, 2016), where reacquiring missing imaging modalities from the same subject is not practical. CBF estimation was better at the posterior regions, where many previous studies (Alsop et al, 2008;Dolui et al, 2017;Huang et al, 2018) and our results showed altered CBF in MCI or Alzheimer's pathology, suggesting the potential use of proposed method in those populations.…”
Section: Discussionsupporting
confidence: 65%
“…The parietal lobe is densely vascularized structure (Clark et al, 2017;Duvernoy et al, 1981;Liebeskind, 2003), which might provide a stronger signal to be estimated. In ASL literature, regions within the parietal lobe are consistently reported to be associated with hypoperfusion in MCI or Alzheimer's disease (Alsop et al, 2010;Dolui et al, 2017). The parietal regions thus might be well-positioned for functional measures captured via fMRI and/or ASL perfusion, which eventually could reflect in our machine learning-based predictions.…”
Section: Better Prediction At the Parietal Lobe Or Regionsmentioning
confidence: 91%
See 1 more Smart Citation
“…We complemented our study of the healthy cohort with multimodal MRI data from 46 cognitively normal elderly subjects (31 female, age = 72.30 ± 6.81 years) from a research study of aging and cognitive impairment conducted at the Penn Memory Center (PMC) and the Alzheimer Disease Core Center (ADCC) at the University of Pennsylvania. All participants had an extensive annual evaluation of medical history, physical examination, neurological history and examination, and psychometric assessment; all of these data are collectively used to determine clinical status (64). The study procedures were approved by the IRB of the University of Pennsylvania.…”
Section: Subjectsmentioning
confidence: 99%
“…At present, due to its higher labeling efficiency, the PCASL is also the recommended ASL implementation for clinical studies (Alsop et al, 2015;Dolui et al, 2017) and can be suitably combined with a 3D readout acquisition scheme (3D-PCASL) to achieve optimal signalto-noise ratio performances (Vidorreta et al, 2013).…”
mentioning
confidence: 99%